Diet of Free Ranging American Mink (Neovison vison) in Denmark - René Worup Rørbæk; Tobias Astell Andersen; Cino Pertoldi; Alex Jørgensen; Sussie Pagh (Animals, 2023)
Non-native American mink (Neovison vison) is a widely spread predator in Denmark. The feral population in mainland Denmark consists of captive-born mink that escaped from fur farms and wild mink born in nature, whereas the population on Bornholm is almost all wild-born mink. In this study, the diets of feral mink in mainland Denmark and on the island of Bornholm are analyzed. The aim of this study was to examine (1) whether the diet of the larger captive-born mink differs from that of the smaller wild-born mink, (2) assess the regional variations between the diets of mink in mainland Denmark and on Bornholm, and (3) investigate the seasonal variation in the diet composition of mink. The stomach contents of 364 mink (243 wild-born and 114 captive-born) culled in the years 2019–2022 were analyzed. Of these, 203 mink were from mainland Denmark, and 154 were from Bornholm. No significant differences were found between the diets of captive-born mink and wild-born mink or the mink found in mainland Denmark and on the island of Bornholm. Significantly more empty stomachs were found during spring than during the summer and autumn, suggesting a bottleneck in the diet during spring.